Foamable urethane resin composition

JP7634947B2Active Publication Date: 2025-02-25SEKISUI CHEMICAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020140447
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-21
Publication Date
2025-02-25
Estimated Expiration
2040-08-21

AI Technical Summary

Benefits of technology

【0006】 本発明によれば、保管時に沈殿物が生じ難く、取り扱い性に優れ、かつ使用時に用いる吹き付け装置などの摩耗を抑制することができる発泡性ウレタン樹脂組成物を提供することができる。これに加えて、該発泡性ウレタン樹脂組成物は、難燃性が良好であり、かつ火災が生じたときなどに、燃え広がり難い性質を備えるポリウレタン発泡体を形成することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634947000001
    Figure 0007634947000001
Patent Text Reader

Abstract

To provide a foamable urethane resin composition for producing a polyurethane foam that resists the spread of a fire without substantially containing an inorganic filler.SOLUTION: A foamable urethane resin composition contains a polyol compound containing a phthalic acid-based polyester polyol, a polyisocyanate compound, a flame retardant that is liquid at room temperature, a foamer, and a catalyst. The foamable urethane resin composition does not substantially contain an inorganic filler and is used for spraying.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a foamable urethane resin composition. [Background technology]

[0002] Polyurethane foams are used in the insulation and prevention of condensation of ceilings, roofs, walls, etc. of buildings such as apartment complexes, detached houses, and commercial buildings, taking advantage of their excellent heat insulating properties. Although polyurethane foams are lightweight, they are organic and therefore flammable. In order to improve this, polyurethane foams containing flame retardants and the like to enhance their flame retardancy are used. For example, Patent Document 1 describes a flame-retardant polyurethane foam obtained by using ammonium polyphosphate, a urea derivative, a polyol, and an isocyanate, characterized in that the flame-retardant polyurethane foam is obtained by using ammonium polyphosphate in the range of 5 to 150 parts by weight and a urea derivative in the range of 0.001 to 15 parts by weight per 100 parts by weight of polyol. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-151524 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there have been a relatively large number of reports of fires caused by polyurethane foams used as thermal insulation materials in buildings. In order to alleviate such problems, it is hoped that polyurethane foams that not only have excellent flame retardancy but also have the property of being less susceptible to the spread of fire when a fire breaks out will be developed. On the other hand, for example, it is expected that the polyurethane foam will be made less susceptible to fire spread by blending a large amount of inorganic filler such as a solid flame retardant. However, blending an inorganic filler can cause problems such as the formation of precipitates during storage of the foamable urethane resin composition used to produce the polyurethane foam, making it difficult to handle, or the equipment used to spray the foamable urethane resin composition becoming more susceptible to wear. Therefore, an object of the present invention is to provide a foamable urethane resin composition for producing a polyurethane foam which is substantially free of inorganic filler, has good flame retardancy, and is resistant to flame spread. [Means for solving the problem]

[0005] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by a foamable urethane resin composition that contains a polyol compound containing a phthalic acid-based polyester polyol, a polyisocyanate compound, a flame retardant that is liquid at room temperature, a blowing agent, and a catalyst, and that is substantially free of an inorganic filler, and have thus completed the present invention. That is, the present invention provides the following items [1] to

[11] . [1] A foamable urethane resin composition comprising a polyol compound containing a phthalic acid-based polyester polyol, a polyisocyanate compound, a flame retardant that is liquid at room temperature, a foaming agent, and a catalyst, the foamable urethane resin composition being substantially free of inorganic filler and used for spray applications. [2] The foamable urethane resin composition according to [1], wherein the catalyst comprises a urethanization catalyst and a trimerization catalyst, the amount of the urethanization catalyst in the foamable urethane resin composition is 0.3 to 22 parts by mass per 100 parts by mass of the polyol compound, and the amount of the trimerization catalyst in the foamable urethane resin composition is 0.3 to 15 parts by mass per 100 parts by mass of the polyol compound. [3] The foamable urethane resin composition according to [2], wherein the mixing ratio of the urethanization catalyst to the trimerization catalyst is 10:1 to 1:10. [4] The foamable urethane resin composition according to [2] or [3], wherein the urethane-forming catalyst contains a bismuth-based catalyst. [5] The foamable urethane resin composition according to any one of [2] to [4], wherein the urethanization catalyst contains an imidazole-based catalyst. [6] The polyurethane foam made of the foamable urethane resin composition is subjected to a test for a radiant heat intensity of 50 kW / m according to the test method of ISO-5660. 2 When heated for 5 minutes, the total heat generated is 8MJ / m 2 The foamable urethane resin composition according to any one of [1] to [5] below: [7] The polyurethane foam made of the foamable urethane resin composition is subjected to a test for a radiant heat intensity of 50 kW / m according to the test method of ISO-5660. 2 The maximum heat generation rate when heated for 5 minutes is 120kW / m 2 The foamable urethane resin composition according to any one of [1] to [6] below: [8] The foamable urethane resin composition according to any one of [1] to [7], wherein the polyol compound contains a polyether polyol and a phthalic acid-based polyester polyol, and the content of the phthalic acid-based polyester polyol is 50 mass% or more based on the total amount of the polyol compounds. [9] The foamable urethane resin composition according to any one of [1] to [8], wherein the foaming agent contains water, and the content of the water is 1.5 parts by mass or less per 100 parts by mass of the polyol compound.

[10] The foamable urethane resin composition according to any one of [1] to [9], wherein the foaming agent contains a hydrofluoroolefin.

[11] The foamable urethane resin composition according to any one of [1] to

[10] , having an isocyanate index of 150 to 700. Effect of the Invention

[0006] According to the present invention, it is possible to provide a foamable urethane resin composition which is less likely to produce precipitates during storage, has excellent handleability, and can suppress wear on a spraying device used during use. In addition, the foamable urethane resin composition can form a polyurethane foam which has good flame retardancy and is less likely to spread fire when a fire occurs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] [Foamable urethane resin composition] The foamable urethane resin composition of the present invention is a foamable urethane resin composition comprising a polyol compound containing a phthalic acid-based polyester polyol, a polyisocyanate compound, a flame retardant that is liquid at room temperature, a foaming agent, and a catalyst, and the foamable urethane resin composition is a foamable urethane resin composition that is substantially free of inorganic filler.

[0008] (Inorganic filler) The foamable urethane resin composition of the present invention is substantially free of inorganic filler. By substantially not containing an inorganic filler, it is possible to provide a foamable urethane resin composition which is less likely to produce precipitates during storage, has excellent handleability, and can suppress wear on tools and the like used during use. Here, substantially no inorganic filler means that the content of inorganic filler is 5% by mass or less, and preferably 1% by mass or less, based on the total amount of the foamable urethane resin composition.

[0009] The inorganic filler is a particulate or fibrous inorganic compound, and examples of the inorganic filler include metals, metal oxides, metal hydroxides, and ceramics. Examples of the inorganic filler include solid flame retardants and inorganic fillers other than solid flame retardants. The solid flame retardant is a flame retardant that is solid at 23° C., and examples thereof include antimony-containing flame retardants such as antimony oxide, antimonate, and pyroantimonate, metal hydroxide-based flame retardants such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, boron-containing flame retardants such as lithium borate and sodium borate, phosphinic acid-based flame retardants, phosphate-containing flame retardants, bromine-containing flame retardants, and red phosphorus. In addition, examples of inorganic fillers other than solid flame retardants include silica, diatomaceous earth, alumina, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, ferrites, basic magnesium carbonate, calcium carbonate, magnesium carbonate, barium carbonate, dawsonite, hydrotalcite, calcium sulfate, barium sulfate, gypsum fiber, potassium salts such as calcium silicate, talc, clay, mica, montmorillonite, bentonite, activated clay, sepiolite, imogolite, sericite, glass fiber, glass beads, silica palan, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon fiber, carbon palan, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, stainless steel fiber, various magnetic powders, slag fiber, fly ash, silica alumina fiber, alumina fiber, silica fiber, zirconia fiber, and the like.

[0010] (Polyol Compound) The polyol compound contained in the foamable urethane resin composition of the present invention contains a phthalic acid-based polyester polyol. By containing a phthalic acid-based polyester polyol as the polyol compound contained in the foamable urethane resin composition, the flame retardancy of the obtained polyurethane foam can be increased, and furthermore, the property of flame spread resistance can be easily ensured. The phthalic acid-based polyester polyol is a condensation product of a phthalic acid selected from o-phthalic acid (phthalic acid), m-phthalic acid (isophthalic acid) and p-phthalic acid (terephthalic acid) with a glycol. The glycol is not particularly limited, but it is preferable to use low molecular weight aliphatic glycols known as components of polyester polyols, such as ethylene glycol, propylene glycol, and diethylene glycol. From the viewpoint of enhancing the flame retardancy of the polyurethane foam and enhancing the flame spread prevention performance, it is more preferable that the phthalic acid-based polyester polyol contained in the polyol compound contains p-phthalic acid-based polyester polyol, which is a condensation product of p-phthalic acid and glycol.

[0011] In a polyurethane foam made from the foamable urethane resin composition of the present invention, from the viewpoint of enhancing the flame retardancy of the polyurethane foam and enhancing the flame spread prevention performance, the content of the phthalic acid-based polyester polyol based on the total amount of polyol compounds is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, and particularly preferably 100 mass%.

[0012] The hydroxyl value of the phthalic acid-based polyester polyol is preferably from 100 to 350 mgKOH / g, and more preferably from 150 to 300 mgKOH / g.

[0013] The foamable urethane resin composition of the present invention may contain other polyol compounds other than phthalic acid-based polyester polyol. The other polyol compounds are not particularly limited, but may include, for example, other polyester polyols other than polyether polyols and phthalic acid-based polyester polyols, and among them, polyether polyols are preferred. By using polyether polyol as the other polyol compound, it is possible to improve the workability during urethane foaming and the adhesion to the target object.

[0014] <Polyether polyol> Polyether polyol is a polyoxyalkylene polyol obtained by ring-opening addition polymerization of an alkylene oxide to an initiator having two or more active hydrogen atoms. Specific examples of the initiator include aliphatic polyhydric alcohols (e.g., glycols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexylene glycol, and cyclohexanedimethanol, triols such as trimethylolpropane and glycerin, tetrafunctional alcohols such as pentaerythritol, and sugars such as sucrose and sorbitol), aliphatic amines (e.g., alkylenediamines such as ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, and neopentyldiamine, and alkanolamines such as monoethanolamine and diethanolamine), and aromatic amines (e.g., aniline, tolylenediamine, xylylenediamine, diphenylmethanediamine, and Mannich condensation products). These may be used alone or in combination of two or more.

[0015] From the viewpoint of improving moldability at the time of injection during urethane foaming and workability at the time of spraying, the polyether polyol is preferably at least one selected from tolylenediamine-based polyether polyols, Mannich-based polyether polyols, sucrose-based polyether polyols, and sorbitol-based polyether polyols. When using these polyether polyols, the content is preferably 5 to 40 mass%, more preferably 10 to 30 mass%, based on the total amount of polyol compounds, from the viewpoint of ensuring moldability, flame retardancy, and flame spread resistance.

[0016] The tolylenediamine-based polyether polyol is a polyether polyol obtained by using tolylenediamine as an initiator. The same applies to sucrose-based polyether polyol and sorbitol-based polyether polyol. The Mannich polyether polyol is a polyether polyol obtained by utilizing the Mannich reaction, which is a Mannich condensation product having two or more hydroxyl groups in the molecule, or an alkylene oxide added to such a Mannich condensation product. More specifically, it is a Mannich condensation product obtained by the Mannich reaction of at least one of phenol and its alkyl-substituted derivatives, formaldehyde and alkanolamine, or a polyether polyol obtained by ring-opening addition polymerization of at least one of ethylene oxide and propylene oxide to this compound.

[0017] The hydroxyl value of the polyether polyol is preferably from 200 to 1,000 mgKOH / g, more preferably from 300 to 600 mgKOH / g, and further preferably from 330 to 470 mgKOH / g. The hydroxyl value is a value measured in accordance with JIS K1557-1:2007.

[0018] <Other polyester polyols> The other polyester polyols are not particularly limited as long as they are known condensates of dicarboxylic acids and glycols, and examples thereof include condensates of aromatic dicarboxylic acids other than phthalic acid, such as naphthalenedicarboxylic acid, and glycols.

[0019] The hydroxyl value of the other polyester polyols is preferably from 100 to 400 mgKOH / g, and more preferably from 150 to 350 mgKOH / g.

[0020] (Polyisocyanate compounds) As the polyisocyanate compound contained in the foamable urethane resin composition, various polyisocyanate compounds having two or more isocyanate groups, such as aromatic, alicyclic, and aliphatic polyisocyanate compounds, can be used. It is preferable to use liquid diphenylmethane diisocyanate (MDI) because of its ease of handling, rapid reaction, excellent physical properties of the resulting polyurethane foam, and low cost. As the liquid MDI, crude MDI (also called polymeric MDI) can be mentioned. Specific examples of commercially available liquid MDI include "44V-10" and "44V-20" (manufactured by Sumika Covestro Urethane Co., Ltd.), and "Millionate MR-200" (Nippon Polyurethane Industry Co., Ltd.). In addition, uretonimine-containing MDI (for example, commercially available product "Millionate MTL": manufactured by Nippon Polyurethane Industry Co., Ltd.) may also be used. In addition, a polyisocyanate compound may be used in which a part of the isocyanate active group is reacted with a hydroxyl group-containing compound to enhance affinity with polyols in advance. In addition to liquid MDI, other polyisocyanate compounds may be used in combination, and as the polyisocyanate compounds to be used in combination, any polyisocyanate compound known in the technical field of polyurethanes can be used without any limitations.

[0021] The isocyanate index of the foamable urethane resin composition of the present invention is preferably in the range of 150 to 700, more preferably 200 to 650, and further preferably 250 to 600. When the isocyanate index is in such a range, good flame retardancy is achieved and flame spread resistance is easily ensured. The isocyanate index (INDEX) is calculated as follows.

[0022] INDEX = equivalents of isocyanate ÷ (equivalents of polyol + equivalents of water) × 100 Where: Isocyanate equivalent number = number of parts of polyisocyanate used x NCO content (%) x 100 / NCO molecular weight Equivalent weight of polyol = OHV × number of parts of polyol used ÷ molecular weight of KOH, OHV is the hydroxyl value of polyol (mgKOH / g), Equivalents of water = parts of water used × number of OH groups in water / molecular weight of water In the above formula, the unit of parts used is weight (g), the molecular weight of the NCO group is 42, the NCO content is the proportion of NCO groups in the polyisocyanate compound expressed as mass%, and for convenience of unit conversion in the above formula, the molecular weight of KOH is 56,100, the molecular weight of water is 18, and the number of OH groups in water is 2.

[0023] (Liquid flame retardant) The foamable urethane resin composition of the present invention contains a flame retardant that is liquid at room temperature. Here, room temperature means 23° C. By containing a liquid flame retardant, the flame retardancy is improved and the property of flame spread is ensured, and the fact that the flame retardant is liquid makes it possible to suppress wear on the equipment and the like used when using the foamable urethane resin composition. Examples of liquid flame retardants include phosphate flame retardants such as monophosphate esters and condensed phosphate esters. Examples of monophosphate esters include, but are not limited to, trimethyl phosphate, triethyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, and tris(β-chloropropyl) phosphate. The condensed phosphate ester is not particularly limited, but examples thereof include resorcinol polyphenyl phosphate (product name: CR-733S), bisphenol A polycresyl phosphate (product name: CR-741), and aromatic condensed phosphate ester (product name: CR747). The content of the liquid flame retardant is preferably 5 to 100 parts by mass, more preferably 10 to 80 parts by mass, and further preferably 20 to 70 parts by mass, based on 100 parts by mass of the polyol compound.

[0024] (foaming agent) Specific examples of the blowing agent include water, low-boiling point hydrocarbons, chlorinated aliphatic hydrocarbon compounds, fluorine compounds, hydrochlorofluorocarbon compounds, hydrofluorocarbons, ether compounds, hydrofluoroolefins, etc. Further examples of the blowing agent include organic physical blowing agents such as mixtures of these compounds, and inorganic physical blowing agents such as nitrogen gas, oxygen gas, argon gas, and carbon dioxide gas. Examples of the low boiling point hydrocarbon include propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, and cycloheptane. Examples of the chlorinated aliphatic hydrocarbon compounds include dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, and isopentyl chloride. The fluorine compound is, for example, CHF 3 , C.H. 2 F 2 , C.H. 3 Examples include F. Examples of the hydrochlorofluorocarbon compounds include trichloromonofluoromethane, trichlorotrifluoroethane, and dichloromonofluoroethane (for example, HCFC141b (1,1-dichloro-1-fluoroethane), HCFC22 (chlorodifluoromethane), and HCFC142b (1-chloro-1,1-difluoroethane)). Examples of the hydrofluorocarbon include HFC-245fa (1,1,1,3,3-pentafluoropropane) and HFC-365mfc (1,1,1,3,3-pentafluorobutane). The ether compound may, for example, be diisopropyl ether. Examples of the hydrofluoroolefin include HFO-1233zd(E) (trans-1-chloro-3,3,3-trifluoropropene), HFO-1234yf (2,3,3,3-tetrafluoro-1-propene), HFO-1336mzz(Z) (cis-1,1,1,4,4,4,-hexafluorobut-2-ene), and HFO-1224yd(Z).

[0025] In the present invention, the blowing agent preferably contains water, and more specifically, a blowing agent containing at least one compound selected from the above-mentioned low-boiling point hydrocarbons, chlorinated aliphatic hydrocarbon compounds, fluorine compounds, hydrochlorofluorocarbon compounds, hydrofluorocarbons, ether compounds, and hydrofluoroolefins in combination with water is preferred. As the water, for example, ion-exchanged water and distilled water can be appropriately used. The amount of water relative to 100 parts by mass of the polyol compound is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.1 parts by mass or more, and preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less. When the content of water is equal to or more than these lower limits, the foamable urethane resin composition is easily foamed, and the density is easily adjusted to a desired range. When the content of water is equal to or less than these upper limits, the flame retardancy is improved and the property of flame spread is easily secured.

[0026] In the present invention, the foaming agent preferably contains a hydrofluoroolefin, and more preferably contains both the hydrofluoroolefin and the above-mentioned water. From the viewpoint of improving flame retardancy, the amount of the hydrofluoroolefin relative to 100 parts by mass of the polyol compound is preferably 10 to 50 parts by mass, more preferably 15 to 45 parts by mass, and even more preferably 25 to 44 parts by mass.

[0027] (catalyst) The foamable urethane resin composition of the present invention contains a catalyst. The catalyst may contain, for example, one or both of a urethanization catalyst and a trimerization catalyst, and it is preferable to contain both. Note that the catalyst contained in the foamable urethane resin composition does not correspond to the inorganic filler in the present invention.

[0028] <Urethane catalyst> The urethanization catalyst is a catalyst that promotes the reaction between the polyol component and the polyisocyanate. Examples of the urethanization catalyst include metal catalysts and amine catalysts, and it is preferable to use a combination of a metal catalyst and an amine catalyst. By using a combination of a metal catalyst and an amine catalyst, the polyol compound and the polyisocyanate compound react and foam immediately after mixing, and the initial activity can be improved. The urethanization catalyst may be used alone or in combination of two or more.

[0029] Metal catalysts Examples of the metal catalyst include metal salts of bismuth, tin, lead, copper, zinc, cobalt, nickel, etc., and metal salts selected from bismuth and tin are more preferred, and from the viewpoint of improving the initial activity, bismuth salts are even more preferred. That is, the metal catalyst is preferably a bismuth catalyst. The metal salt is preferably an organic acid metal salt, more preferably a metal salt of a carboxylic acid having 5 or more carbon atoms. The carboxylic acid has 5 or more carbon atoms, which improves stability with a blowing agent, particularly hydrofluoroolefin. In addition, the carbon number of the carboxylic acid is preferably 18 or less, more preferably 12 or less, from the viewpoint of catalytic activity, etc. The carboxylic acid is preferably an aliphatic carboxylic acid, and more preferably a saturated aliphatic carboxylic acid. The carboxylic acid may be linear or may have a branched structure, but it is preferable that it has a branched structure. Specific examples of carboxylic acids include octyl acid, lauric acid, versatic acid, pentanoic acid, and acetic acid, and among these, octyl acid is preferred. That is, the transition metal salt is preferably a metal salt of octyl acid. These carboxylic acids may be linear as described above, but may also have a branched structure. An example of an octyl acid having a branched structure is 2-ethylhexanoic acid. As the metal salt of carboxylic acid, bismuth salt of carboxylic acid and tin salt of carboxylic acid are preferable, and among them, bismuth salt of octylic acid is preferable. In addition, the metal salt of carboxylic acid may be a carboxylate of an alkyl metal. For example, the tin salt of carboxylic acid may be a dialkyltin carboxylate, and preferably is a dioctyltin carboxylate. Specific examples of metal salts of carboxylic acids include bismuth trioctate, dioctyltin versatate, dibutyltin dilaurate, dioctyltin dilaurate, and tin dioctylate. Of these, bismuth tris(2-ethylhexanoate), bismuth trioctate, and dioctyltin versatate are preferred, and bismuth tris(2-ethylhexanoate) and bismuth trioctate are more preferred.

[0030] Amine catalyst Examples of the amine catalyst include pentamethyldiethylenetriamine, triethylamine, N-methylmorpholine bis(2-dimethylaminoethyl)ether, bis(2-dimethylaminoethyl)ether, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N'-trimethylaminoethyl-ethanolamine, bis(2-dimethylaminoethyl)ether, N-methyl-N',N'-dimethylaminoethylpiperazine, 1-methylimidazole, 1,2-dimethylimidazole, 1-isobutyl-2-methylimidazole, imidazole compounds such as imidazole compounds in which the secondary amine functional group in the imidazole ring is substituted with a cyanoethyl group, N,N-dimethylcyclohexylamine, diazabicycloundecene, guanidine derivatives, triethylenediamine, tetramethylethylenediamine, tetramethylhexamethylenediamine, trimethylaminoethylpiperazine, tripropylamine, and the like. Acid-blocked products of these amino compounds can also be used. Here, examples of the acid-blocked amino compound include those obtained by blocking an amino compound with a carboxylic acid such as formic acid, acetic acid, propionic acid, oxalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, octylic acid, and 2-ethylhexanoic acid.

[0031] The amount of the urethane catalyst in the foamable urethane resin composition is not particularly limited, but is preferably in the range of 0.3 to 22 parts by mass, more preferably in the range of 1 to 20 parts by mass, and even more preferably in the range of 3 to 18 parts by mass, relative to 100 parts by mass of the polyol compound. By keeping the amount within the above range, the reaction between the polyol compound and the polyisocyanate compound can be promoted at an appropriate reaction rate. When a bismuth-based catalyst is contained as the urethanization catalyst, the amount of the bismuth-based catalyst in the foamable urethane resin composition is not particularly limited, but is preferably in the range of 0.1 to 15 parts by mass, more preferably in the range of 0.3 to 13 parts by mass, and even more preferably in the range of 0.5 to 11 parts by mass, per 100 parts by mass of the polyol compound. When an imidazole compound is contained as a urethanization catalyst, the amount of the imidazole compound in the foamable urethane resin composition is not particularly limited, but is preferably in the range of 1 to 15 parts by mass, more preferably in the range of 2 to 13 parts by mass, and even more preferably in the range of 3 to 11 parts by mass, per 100 parts by mass of the polyol compound.

[0032] <Trimerization catalyst> A trimerization catalyst is a catalyst that promotes trimerization to form an isocyanurate bond. By promoting trimerization of a polyurethane resin, the flame retardancy of a polyurethane foam is improved. Examples of the trimerization catalyst include aromatic compounds such as tris(dimethylaminomethyl)phenol, 2,4-bis(dimethylaminomethyl)phenol, and 2,4,6-tris(dialkylaminoalkyl)hexahydro-S-triazine, alkali metal salts such as potassium acetate, sodium acetate, potassium 2-ethylhexanoate, sodium 2-ethylhexanoate, potassium octylate, and sodium octylate, aziridines such as 2-ethylaziridine, lead compounds such as lead naphthenate and lead octylate, alcoholates such as sodium methoxide, phenolates such as potassium phenoxide, tertiary ammonium salts such as trimethylammonium salts, triethylammonium salts, and triphenylammonium salts, and quaternary ammonium salts such as tetramethylammonium salts, tetraethylammonium, and tetraphenylammonium salts. Examples of the ammonium salts include ammonium salts of carboxylic acids such as 2,2-dimethylpropanoic acid, and more specifically, quaternary ammonium salts of carboxylic acids. The trimerization catalyst may be used alone or in combination of two or more kinds.

[0033] The amount of the trimerization catalyst is not particularly limited, but is preferably in the range of 0.3 to 15 parts by mass, more preferably in the range of 1 to 13 parts by mass, and even more preferably in the range of 2 to 11 parts by mass, relative to 100 parts by mass of the polyol compound. By setting the amount of the trimerization catalyst within the above range, isocyanurate bonds are appropriately formed, and flame retardancy is improved.

[0034] In addition, the total amount of catalysts in the foamable urethane resin composition is preferably 0.5 to 30 parts by mass, more preferably 1 to 25 parts by mass, and even more preferably 2 to 22 parts by mass, relative to 100 parts by mass of the polyol compound, from the viewpoint of improving the urethane curing speed and flame retardancy. When the total amount of catalysts in the foamable urethane resin composition is equal to or more than the above lower limit, the cream time is shortened (for example, 6 seconds or less), and dripping can be prevented when the foamable urethane resin composition is used for spraying. When the total amount of catalysts in the foamable urethane resin composition is equal to or less than the above upper limit, the effect of flame retardancy of the foamable urethane resin composition can be satisfactorily exhibited.

[0035] The blend ratio of the urethanization catalyst to the trimerization catalyst in the foamable urethane resin composition is preferably 10:1 to 1:10, more preferably 8:2 to 2:8, and even more preferably 7:3 to 3:7. By having the blend ratio of the urethanization catalyst to the trimerization catalyst within the above range, the curing speed and flame retardancy of the urethane can be improved in a well-balanced manner.

[0036] (Foam stabilizer) The foamable urethane resin composition may contain a foam stabilizer as required. As the foam stabilizer, a compound having a polar part and a non-polar part in the molecule and having a surface active effect may be preferably used, and examples thereof include surfactants such as polyoxyalkylene foam stabilizers such as polyoxyalkylene alkyl ethers and silicone foam stabilizers such as organopolysiloxanes. In addition, the silicone foam stabilizer may contain a graft copolymer of polydimethylsiloxane and polyethylene glycol. The content of the foam stabilizer is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 8 parts by mass, and further preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the polyol compound. The foam stabilizer may be used alone or in combination of two or more kinds.

[0037] The foamable urethane resin composition can contain, as additives, for example, phenol-based, amine-based, sulfur-based and other antioxidants, heat stabilizers, light stabilizers, metal damage inhibitors, antistatic agents, crosslinking agents, lubricants, softeners, pigments, dyes, gas collectors, tackifying resins, and the like, within the scope of not impairing the effects of the present invention.

[0038] The foamable urethane resin composition of the present invention may be a one-component type, but the foamable urethane resin composition of the present invention is cured by the reaction of the polyol compound and the polyisocyanate compound, so that the viscosity changes with time. Therefore, before using the composition, the composition is divided into two or more parts to prevent the composition from reacting and curing. Then, when using the composition, it is preferable to mix the two or more divided parts of the composition.

[0039] When the foamable urethane resin composition of the present invention is divided into two or more components, each component of the composition divided into two or more components does not start curing by itself, but each component of the composition is divided so that the curing reaction starts after mixing the components of the composition. Usually, a two-component type in which the composition is divided into a polyol composition containing a polyol compound and a polyisocyanate composition containing a polyisocyanate compound is preferred. In this specification, the foamable urethane resin composition is also intended to include the one divided into two or more components when it is divided into two or more components, such as a two-component type.

[0040] The above-mentioned flame retardant, blowing agent, catalyst, and foam stabilizer that is added as necessary, which are liquid at room temperature, may be contained in the polyol composition, may be contained in the polyisocyanate composition, or may be provided separately from the polyol composition and the polyisocyanate composition, but are preferably contained in the polyol composition.

[0041] (Viscosity of polyol composition) The viscosity of the polyol composition at 25°C is not particularly limited, but is preferably 2,000 mPa·s or less, and more preferably 1,000 mPa·s or less. By making the viscosity of the polyol liquid agent below the upper limit value, the fluidity of the foamable urethane resin composition is improved, and mixing defects can be suppressed. The viscosity of the polyol composition can be appropriately adjusted, for example, depending on the molecular weight of the polyol compound used. The viscosity of the polyol composition was measured using a B-type viscometer at a temperature of 25°C.

[0042] The foamable urethane resin composition of the present invention can form a polyurethane foam by foaming and curing. Fires caused by polyurethane foam are mainly caused by sparks and fireballs (lumps of iron heated to high temperatures) during welding and cutting. According to the findings of the present inventors, when a fireball comes into contact with polyurethane foam, it melts the resin and advances inside, resulting in the risk of ignition and spread of fire from inside the polyurethane foam. The hot steel ball evaluation described below reproduces and evaluates fires caused by polyurethane foam during welding and cutting, and can evaluate whether polyurethane foam is resistant to fire spread.

[0043] (Hot steel ball evaluation) For a polyurethane foam made from the foamable urethane resin composition of the present invention, the sinking distance and melting diameter distance of a steel ball are measured by the following procedures (1) to (3). (1) The polyurethane foam is cut into a cube with side dimensions of 50 mm x 50 mm x 50 mm to be used as the test specimen. (2) Place a steel ball with a diameter of 10.0 mm and a weight of 4.15 g in an electric furnace set to a temperature of 800°C, and leave it for 10 minutes or more until the entire steel ball is heated evenly and turns red, bringing the steel ball temperature to 800°C. Note that new steel balls are used. (3) In an atmosphere of 23°C, the steel ball heated in (2) above is immediately placed on the center of the upper part of the test piece in (1) above and left there until the steel ball has completely sunk in. Next, the cross section of the test piece that has been sufficiently cooled is cut and the sinking distance of the steel ball is measured. In this hot steel ball evaluation, the time from heating the steel ball to placing it on the test piece is within 1 second. The steel ball used is made of SUS304. Regarding the electric furnace, for example, a small programmable electric furnace (product name: MMF-1, manufactured by AS ONE Corporation) with inner dimensions of 120 mm×150 mm×100 mm is used.

[0044] In the above hot steel ball evaluation, a cavity is formed in the test specimen from the top surface to the inside due to the sinking of the steel ball. The sinking distance of the steel ball means the maximum distance of the cavity in the vertical direction to the top surface of the test specimen. Note that parts that have discolored due to heat but retain their shape are not included in the measurement of the sinking distance. The fusion diameter distance is the diameter of the hole formed by the heated steel ball on the top surface of the test piece. If the shape of the hole formed on the top surface of the test piece is circular, the diameter of the circle means the diameter of the circle, and if the shape of the hole is elliptical, the diameter of the hole means the major axis. If the shape of the hole is other than circular or elliptical, the maximum distance between any two points on the shape is the diameter of the hole. If the steel ball remains on the surface of the test piece, the test piece does not melt, and no cavity is formed on the top surface, the diameter of the carbonized or discolored part is measured in the same manner as when a cavity is formed.

[0045] The polyurethane foam made of the foamable urethane resin composition preferably has a steel ball sinking distance of 10 mm or less in a hot steel ball test. If the steel ball sinking distance exceeds 10 mm, the polyurethane foam is likely to spread when exposed to a fire or the like, making it difficult to effectively prevent the fire from spreading. From the viewpoint of effectively preventing the fire from spreading, the steel ball sinking distance is preferably 5 mm or less, more preferably 3 mm or less, and even more preferably 0 mm.

[0046] The polyurethane foam made of the foamable urethane resin composition preferably has a melt diameter distance of 15 mm or less in a hot steel ball test. By having a melt diameter distance of 15 mm or less, the polyurethane foam is less likely to spread fire when exposed to a fire or the like, and the spread of fire can be effectively prevented. From the viewpoint of effectively preventing the spread of fire, the melt diameter distance is preferably 14 mm or less, more preferably 13 mm or less, and even more preferably 12 mm or less. The melt diameter distance is 0 mm or more.

[0047] By having the steel ball sinking distance and melting diameter distance in the hot steel ball evaluation of a polyurethane foam made from the foamable urethane resin composition of the present invention fall within the above-mentioned specified ranges, the polyurethane foam can be made less susceptible to fire spreading when exposed to a fire, etc. The steel ball sinking distance and molten diameter distance can be adjusted to desired values ​​by adjusting the type of polyol compound contained in the foamable urethane resin composition, the water content, and the like.

[0048] (Vertical Burning Evaluation) The polyurethane foam made of the foamable urethane resin composition of the present invention was evaluated for vertical flammability by the following procedures (1) to (3). (1) A rod-shaped sample with dimensions of 100 mm x 10 mm x 10 mm is cut out of the polyurethane foam to serve as a test specimen. (2) The bottom end of the vertically held rod-shaped sample is exposed to a propane gas burner with a flame length of 20 mm for 10 seconds. (3) The state of flame spread of the rod-shaped sample exposed to the flame in (2) above is evaluated. The polyurethane foam made of the foamable urethane resin composition is preferably one in which the flame reach distance in the flame spread state in the vertical combustion evaluation is 100 mm or less. When the flame spread state is 100 mm or less, the polyurethane foam is less likely to spread when exposed to a fire or the like, and the spread of the fire can be effectively prevented. From the viewpoint of effectively preventing the spread of the fire, the flame spread state is preferably 75 mm or less, more preferably 50 mm or less.

[0049] (Total heat generation) The polyurethane foam made of the foamable urethane resin composition of the present invention was subjected to a test for a radiation heat intensity of 50 kW / m according to the test method of ISO-5660. 2 When heated for 5 minutes, the total heat generated is 8MJ / m 2 The total calorific value is preferably 8MJ / m or less. 2 The polyurethane foam made of the foamable urethane resin composition of the present invention has a predetermined flame retardancy because the polyurethane foam has the predetermined flame retardancy and, as described above, the steel ball sinking distance and the melting diameter distance are equal to or less than certain values, so that the polyurethane foam has both flame retardancy and the property of not spreading fire, and can more effectively prevent the spread of fire in the event of a fire. From the viewpoint of further improving the flame retardancy of the polyurethane foam, the total calorific value is set to 7.8 MJ / m 2 It is preferable that the concentration is less than 7.5 MJ / m 2 It is more preferable that:

[0050] (Maximum heat generation rate) The polyurethane foam made of the foamable urethane resin composition of the present invention was subjected to a test for a radiation heat intensity of 50 kW / m according to the test method of ISO-5660. 2 The maximum heat generation rate when heated for 5 minutes is 120kW / m 2 It is preferable that the maximum heat generation rate is 120 kW / m or less. 2 The polyurethane foam made of the foamable urethane resin composition of the present invention has a predetermined flame retardancy by being as described below. In addition, by adjusting both the maximum heat release rate and the total heat release amount as described above, the flame retardancy is further improved. By having a predetermined flame retardancy and, as described above, having the steel ball sinking distance and molten diameter distance below certain values, a polyurethane foam is obtained that has both flame retardancy and the property of not spreading fire, and can more effectively prevent the spread of fire in the event of a fire. From the viewpoint of further improving the flame retardancy of polyurethane foam, the maximum heat generation rate is set to 98 kW / m 2 It is preferable that the maximum power consumption is 95 kW / m or less. 2It is more preferable that:

[0051] The total heat release amount and maximum heat release rate can be obtained by a cone calorimeter test, and specifically, can be measured by the method described in the Examples. In the above-mentioned cone calorimeter test, it is preferable that the polyurethane foam used in the test has a shape stability to such an extent that it does not come into contact with the spark igniter of the cone calorimeter. The polyurethane foams used in the cone calorimeter test are prepared under the conditions described in the Examples. Specifically, polyurethane foams prepared by hand mixing foaming and polyurethane foams prepared by spray foaming are used.

[0052] (Initial activity) The cream time of the foamable urethane resin composition of the present invention is not particularly limited, but is preferably 6 seconds or less, more preferably 5 seconds or less, and even more preferably 4 seconds or less at a liquid temperature of 10° C. When the cream time is within the above range, the initial activity is good, and dripping can be prevented when the foamable urethane resin composition is used for spray applications. The cream time refers to the time from when the polyol compound and the polyisocyanate compound are started to be mixed by stirring until the mixture becomes cloudy and creamy and immediately before it starts to expand. The polyurethane foam used for measuring the cream time is prepared by the hand mixing foaming method described in the Examples.

[0053] [Polyurethane foam] The polyurethane foam of the present invention is formed from the above-mentioned foamable urethane resin composition, specifically, is obtained by foaming and curing the foamable urethane resin composition.

[0054] (density) The density of the polyurethane foam made from the foamable urethane resin composition of the present invention is not particularly limited, but is preferably 20 to 200 kg / m 3It is preferable that the density is in the range of 200 kg / m 3 By setting the density to 20kg / m or less, the polyurethane foam becomes lighter and easier to apply to structures. 3 From these viewpoints, the density of the polyurethane foam is preferably 25 to 100 kg / m 3 More preferably, the range is 25 to 80 kg / m 3 It is more preferable that the density of the polyurethane foam is in the range of 9. The density of the polyurethane foam can be measured in accordance with JIS K7222. The polyurethane foam used for density measurement is prepared by hand mixing foaming as described in the Examples.

[0055] The foam of the present invention is not particularly limited, but when it is divided into two or more parts, such as a two-liquid type foamable urethane resin composition, for example, a polyol composition and a polyisocyanate composition, which are prepared by mixing each component in advance, are prepared in two or more parts, and then mixed and foamed. The mixing and foaming of each component can be performed by a known method. For example, it can be obtained using a known device such as a high-pressure foaming machine, a low-pressure foaming machine, a spray foaming machine, or a hand mixer. In addition, in the case of a one-liquid type, a method of foaming a foamable urethane resin composition obtained by mixing each component constituting the foamable urethane resin composition by a known method can be mentioned.

[0056] (Application) The uses of the foamable urethane resin composition of the present invention and the above-mentioned polyurethane foam are not particularly limited, but they can be used for spraying to fill cavities in structures such as buildings, furniture, automobiles, trains, ships, etc., or for spraying onto the structures. Among these, the use for spraying onto structures, i.e., as a foamable urethane resin composition for spraying, is preferred. Spraying can be performed using a spraying device (e.g., A-25 manufactured by GRACO) and a spray gun (e.g., D-gun manufactured by Gasmar). A general spraying device and a spray gun spray the foaming liquid by reacting the isocyanate and polyol in an even volume ratio, so that the foaming liquid can be reacted in a volume ratio of 1.0 isocyanate to 0.8 to 1.2 polyol. Spraying can be performed by adjusting the temperature of a polyol composition and a polyisocyanate composition in separate containers in a spraying device, colliding and mixing the two at the tip of a spray gun, and turning the mixed liquid into mist by air pressure. The spraying device and the spray gun are known, and commercially available products can be used. EXAMPLES

[0057] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.

[0058] Details of each component used in each example and comparative example are as follows. (1) Polyol compounds p-Phthalic acid-based polyester polyol (Kawasaki Chemical Industries, Ltd., product name: RFK-509, hydroxyl value = 200 mg KOH / g) p-Phthalic acid-based polyester polyol (Hitachi Chemical Co., Ltd., product name: SV-208, hydroxyl value = 235 mg KOH / g) Mannich polyether polyol (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: DK3776, hydroxyl value = 350 mg KOH / g) Tolylenediamine-based polyether polyol (Mitsui Chemicals, product name: GR-40A, hydroxyl value = 400 mg KOH / g) Sucrose-based polyether polyol (AGC, product name: EL-100S, hydroxyl value = 450 mg KOH / g) Sorbitol-based polyether polyol (Mitsui Chemicals, product name: Actocol SOR400, hydroxyl value = 400 mg KOH / g) Ethylenediamine polyether polyol (AGC, product name: Exenol 750ED, hydroxyl value = 760 mg KOH / g) (2) Liquid flame retardants Phosphate ester flame retardant <Tris(β-chloropropyl)phosphate> (manufactured by Daihachi Chemical Industry Co., Ltd., product name: TMCPP) (3) Foam stabilizer Silicone foam stabilizer (Toray Dow Corning, product name: SH-193) (4) Catalyst (i) Trimerization catalyst Quaternary ammonium salt <2,2-dimethylpropanoic acid tetramethylammonium salt> (manufactured by Evonik Japan, product name: TMR-7), concentration 45 to 55% by mass (ii) Urethane catalyst Imidazole compound <1,2-dimethylimidazole> (Kao Corporation, product name: Kao Raiser NO390), concentration 65-75% by mass Bismuth compound <Bismuth tris(2-ethylhexanoate)> (Shepherd Chemical, product name: BiCAT8210), concentration 80-90% by mass (5) Foaming agent ·water HFO-1233zd <hydrofluoroolefin> (Honeywell product name: Solstice LBA) (6) Polyisocyanate compounds MDI (manufactured by Sumika Covestro Urethane Co., Ltd., product name: 44V-20)

[0059] Details of the foaming method for the polyurethane foams produced in each of the Examples and Comparative Examples are as follows.

[0060] <Hand mixing foam> The polyurethane foams produced in each Example and Comparative Example were prepared by adding a mixture of a polyol compound, a liquid flame retardant, a foam stabilizer, a catalyst, and a blowing agent in the proportions shown in Table 1, and a polyisocyanate compound (total amount 200 g, liquid temperature 10°C) to a polypropylene beaker and stirring with a lab-di-spar for 3 seconds.Then, the mixture was immediately sprayed on a gypsum board with a thickness of 12.5 mm to obtain a polyurethane foam.

[0061] <Spray foaming> The polyurethane foams produced in each of the Examples and Comparative Examples were prepared by spraying the foamable urethane resin composition onto a 12.5 mm gypsum board using a spraying device (A-25 manufactured by GRACO) and a spray gun (D gun manufactured by Gasmar Co., Ltd.) in the same manner as above, in accordance with the formulation in Table 1. The temperature of the raw solution at this time was 40°C.

[0062] The methods for measuring the various physical properties and characteristics are as follows.

[0063] [Hot steel ball evaluation] For the polyurethane foams produced in each of the Examples and Comparative Examples, the sinking distance and fusion diameter distance of the steel ball were measured by the following procedures (1) to (3). (1) The polyurethane foam was cut into a cube with side dimensions of 50 mm x 50 mm x 50 mm to prepare a test specimen. (2) A steel ball with a diameter of 10.0 mm and a weight of 4.15 g was placed in an electric furnace set to a temperature of 800°C, and left for 15 minutes until the entire steel ball was heated uniformly and turned red, at which point the temperature of the steel ball reached 800°C. Note that new steel balls were used. (3) In an atmosphere of 23°C, the steel ball heated in (2) above was immediately placed on the center of the upper part of the test piece in (1) above and left there until the steel ball had completely sunk in. Then, the cross section of the sufficiently cooled test piece was cut and the sinking distance of the steel ball was measured. In this hot steel ball evaluation, the time from heating the steel ball to placing it on the test piece was within 1 second. The steel ball used was made of SUS304. Regarding the electric furnace, for example, a small programmable electric furnace (product name: MMF-1, manufactured by AS ONE Corporation) with inner dimensions of 120 mm×150 mm×100 mm was used. From the obtained sinking distance and molten diameter distance of the steel ball, the quality of the flame-proof property was judged as follows.

[0064] <Hot steel ball evaluation criteria> ○ The steel ball sinking distance is 5mm or less and the fusion diameter distance is 15mm or less △: The steel ball sinks below 5mm and is 10mm or more ×: Anything other than the above "〇" or "△"

[0065] [Vertical combustion evaluation] The polyurethane foams produced in the respective Examples and Comparative Examples were evaluated for vertical flammability according to the following procedures (1) to (3). (1) A rod-shaped sample with dimensions of 100 mm x 10 mm x 10 mm is cut out of the polyurethane foam to serve as a test specimen. (2) The lower end of the vertically held rod-shaped sample is brought into contact with a propane gas burner with a flame length of 20 mm. (3) The state of flame spread of the rod-shaped sample exposed to the flame in (2) above is evaluated.

[0066] <Vertical Combustion Evaluation Standard> ○ Flame spread is less than 100 mm △ Flame spread is 100mm or more × Flame spread is 100mm or more and almost no combustion residue remains

[0067] [Maximum heat release rate, total heat release] The polyurethane foam adhered to the gypsum board as a base was cut into a size of 10 cm in length, 10 cm in width and 3.25 cm in thickness (including 12.5 mm gypsum board) to prepare a sample for cone calorimeter testing, and a cone calorimeter test was carried out. The test sample was subjected to a radiant heat intensity of 50 kW / m2 in accordance with the ISO-5660 test method. 2 The maximum heat release rate and total heat release amount were measured when the sample was heated at 40°C for 5 minutes.

[0068] [Initial activity evaluation] The cream time of the foamable urethane resin composition prepared in each Example and Comparative Example was evaluated by the following method. A mixture obtained by mixing a polyol compound, a liquid flame retardant, a foam stabilizer, a catalyst, and a foaming agent in the proportions shown in Table 1 and a polyisocyanate compound (total amount 200 g, liquid temperature 10°C) were added to a polypropylene beaker and stirred for 3 seconds with a lab-di-spar. The cream time of the obtained mixture was measured and evaluated as follows.

[0069] Cream Time The cream time (at a liquid temperature of 10°C) of the foamable urethane resin composition prepared by the above method was measured. A foamable urethane resin composition with a short cream time has good initial activity and can prevent dripping when used for spray applications. The cream time can be measured as the time when the color of the mixture solution begins to change with the naked eye. ○ Cream time is 4 seconds or less △ Cream time is between 4 and 6 seconds × Cream time is over 6 seconds

[0070] [density] The density of each of the foamable urethane resin compositions prepared in the examples and comparative examples was measured in accordance with JIS K7222:2005.

[0071] [Example 1] According to the formulation in Table 1, the polyol compound, liquid flame retardant, foam stabilizer, catalyst, and foaming agent were weighed into a 1000 mL polypropylene beaker and stirred with a hand mixer at 20°C for 10 seconds to prepare a polyol composition. The polyol composition was then cooled to 10°C, and a polyisocyanate composition (polyisocyanate compound) adjusted to the same temperature of 10°C was added to prepare a foamable urethane resin composition. The composition was stirred with a lab-di spar for 3 seconds to prepare a polyurethane foam. The polyurethane foam was used to carry out the hot steel ball evaluation described above. The maximum heat release rate, total heat release amount, initial activity evaluation, and vertical combustion evaluation were also evaluated by the above-mentioned procedures. The various evaluation results are shown in Table 1.

[0072] [Examples 2 to 18, Comparative Examples 1 to 2] A polyurethane foam was obtained in the same manner as in Example 1, except that the formulation was changed as shown in Table 1. The polyurethane foam was subjected to the above-mentioned hot steel ball evaluation. The maximum heat release rate, total heat release amount, initial activity evaluation, and vertical combustion evaluation were also evaluated by the above-mentioned procedures. The results of each evaluation are shown in Table 1. Examples 2 and 4 were evaluated by spray foaming.

[0073] [Table 1]

[0074] As shown in each example, the polyurethane foam formed by the foamable urethane resin composition of the present invention has a low maximum heat release rate and a low total heat release amount, and has a good vertical combustion evaluation, which indicates that it has excellent flame retardancy. In addition, the polyurethane foam formed by the foamable urethane resin composition of the present invention has a short steel ball sinking distance and a short melting diameter distance, which indicates that it has a property of being difficult to spread fire. Furthermore, since the foamable urethane resin composition of the present invention does not substantially contain an inorganic filler, it is difficult to produce precipitates during storage, is easy to handle, and can suppress wear of a spraying device used during use. Furthermore, the foamable urethane resin composition of the present invention has a good initial activity, and can prevent dripping when used for spraying purposes.

Claims

1. A foamable urethane resin composition comprising a polyol compound containing a phthalic acid-based polyester polyol, a polyisocyanate compound, a flame retardant that is liquid at room temperature, a foaming agent, and a catalyst, the catalyst comprises a urethanization catalyst and a trimerization catalyst; The urethane-forming catalyst includes a bismuth-based catalyst and an imidazole-based catalyst, the trimerization catalyst comprises a quaternary ammonium salt; The blowing agent comprises a hydrofluoroolefin; the polyol compound contains a polyether polyol and a phthalic acid-based polyester polyol, and the content of the phthalic acid-based polyester polyol is 50 mass% or more based on the total amount of the polyol compound; The foamable urethane resin composition has an inorganic filler content of 5 mass% or less and is used for spraying with a spray gun.

2. the amount of the urethanization catalyst in the foamable urethane resin composition is 0.3 to 22 parts by mass based on 100 parts by mass of the polyol compound, 2. The foamable urethane resin composition according to claim 1, wherein the amount of the trimerization catalyst in the foamable urethane resin composition is 0.3 to 15 parts by mass per 100 parts by mass of the polyol compound.

3. 3. The foamable urethane resin composition according to claim 2, wherein the mixing ratio of said urethanization catalyst to said trimerization catalyst is 10:1 to 1:

10.

4. The polyurethane foam made of the foamable urethane resin composition was subjected to a test with a radiant heat intensity of 50 kW / m2 in accordance with the ISO-5660 test method. 2 When heated for 5 minutes, the total heat generation is 8 MJ / m 2 The foamable urethane resin composition according to any one of claims 1 to 3, wherein:

5. The polyurethane foam made of the foamable urethane resin composition was subjected to a test with a radiant heat intensity of 50 kW / m2 in accordance with the ISO-5660 test method. 2 The maximum heat generation rate when heated for 5 minutes is 120 kW / m 2 The foamable urethane resin composition according to any one of claims 1 to 4, wherein:

6. The foamable urethane resin composition according to any one of claims 1 to 5, wherein the foaming agent contains water, and the content of the water is 1.5 parts by mass or less per 100 parts by mass of the polyol compound.

7. The foamable urethane resin composition according to any one of claims 1 to 6, having an isocyanate index of 150 to 700.

Citation Information

Patent Citations

  • Spraying insulating material

    JP2005307147A

  • Flame retardant polyurethane foam

    JP2015151524A

  • Heat insulation laminate

    JP2019064263A

  • Hard polyurethane foam

    JP2019214651A

  • Mixed liquid agent, polyurethane composition, cartridge container for caulk gun, pressure resistant container for spraying, and mixing system

    JP2020090582A